I'm your peanut butter big brother - Alko, Selina (New York : Alfred A. Knopf, 2009)
A child in an interracial family wonders what his yet-to-be-born sibling will look like.
Keywords: Multiracial people -- Fiction; Babies -- Fiction; Brothers and sisters -- Fiction; Multiracial people -- Juvenile fiction; Infants -- Juvenile fiction; Siblings -- Juvenile fiction